Quality of statistical match and simulations used in the estimation of the Levy Institute Measure of Time and Consumption Poverty (LIMTCP) for Turkey in 2006 - Thomas Masterson (Levy Economics Institute of Bard College, 2013)
The quality of match of the statistical match used in the Levy Institute Measure of Time and Consumption Poverty (LIMTCP) estimates for Turkey in 2006 is described. The match combines the 2006 Zaman Kullanim Anketi (ZKA 2006) with the 2006 Hanehalki Bütçe Anketi (HBA 2006). These are the national time-use survey and household income and expenditure surveys, respectively. The alignment of the two datasets is examined, after which various aspects of the match quality are detailed. The match is of high quality, given the nature of the source datasets. The quality of the simulation of employment gains for Turkey in 2006 is then described. All eligible adults not working for pay, as employers, or as unpaid household workers were assigned jobs. In all households that included job recipients, the time spent on household production was imputed for everyone included in the time-use survey. Household consumption was then assigned to each household in the simulation containing a job recipient. The recipient group was compared to the donor group, both in terms of demographic similarity and in terms of the imputed usual hours, earnings, and household production generated in the simulation. In both cases, the simulations were of reasonable quality, given the nature of the challenges in assessing their quality.
Keywords: C14; C40; D31; J22; 330; Statistical Matchin; Labor Force Simulation; Time Use; Household Production; Poverty; Levy Institute Measure of Time and Consumption Poverty; LIMTCP; Turkey